Analysis Of Internal Control System In The Revenue Cycle (Case Study Of Pt Btj Farma) - Rijal, Muhammad Khoerur; Firmanto , Yuki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine and analyze the implementation of internal control in the revenue cycle of PT Berkah Tio Jaya Farma based on COSO (Committee of Sponsoring Organization of Treadway Commission). This type of research is qualitative research using a descriptive research approach. The analysis method in this study is by literature study by studying literature related to the internal control system in the revenue cycle, interviews and direct observation. The results of the study stated that there were several weaknesses in internal control, from 87 focus points from COSO, 56 focus points had not been applied to the revenue cycle of PT BTJ Farma. The elements with the most deficiencies were in the risk assessment element and the monitoring element. The conclusion is that the Control variable and the Efficiency variable need to be prioritized for improvement by the company because these variables have many weaknesses and their role is very vital for the implementation of the revenue cycle of PT BTJ Farma.